Analisis Perbandingan Metode Pendukung Keputusan Pemilihan Kos Mahasiswa di Pontianak - Noerul Hanin; David Jordy Dhandio; Della Zaria (UIN Sunan Kalijaga Yogyakarta, 2023)
The existence of boarding houses in public spaces is highly expected by the community, especially migrants such as students who need a temporary house in oversea areas. In Pontianak, especially around Tanjungpura University, there are many boarding houses that offer various facilities with various rental prices. Thus, decision support analysis is needed to choose a good boarding house for students around Tanjungpura University. In this study, two decision support system methods were selected, those are SAW and TOPSIS. These two methods were chosen because they have uncomplicated calculations, but are capable to produce good decisions. A comparison of the two methods was carried out to find out differences in results and calculation concepts to choose boarding houses for students in Pontianak. Data that was used for the trial were 10 alternative boarding houses located around the university. Based on trial results, the best boarding house obtained using SAW and TOPSIS methods is Yoga Kost.